Molybdenum-based nanoclusters act as antioxidants and ameliorate acute kidney injury in mice - Dalong Ni (Nature Portfolio, 2018)
There are currently no effective therapies available for acute kidney injury (AKI). Here the authors generate molybdenum-based polyoxometalate nanoclusters and show that these have preferential renal uptake and can ameliorate AKI pathology in mice by scavenging reactive oxygen species.